Dispatches from the age of crocodiles: New discoveries from ancient lineages. Issue 10 (1st August 2022) - Holliday, Casey M.; Schachner, Emma R.
Abstract: Crocodilians inspire researchers and the public alike with their explosive hunting methodologies, distinct craniofacial and dental morphology, and resplendent fossil record. This special issue highlights recent advances in the biology and paleontology of this fascinating lineage of vertebrates. The authors in this volume bring crocodylians and their extinct ancestors to life using a variety of approaches including fieldwork, imaging, 3D modeling, developmental biology, physiological monitoring, dissection, and a host of other comparative methods. Our journey begins with early crocodylomorphs from the Triassic, carries us through the radiation of crocodyliforms during the rest of the Mesozoic Era, and finally celebrates the diversification development and biology of extant crocodylians. Crocodyliform science has grown appreciably the past few decades. New fossil species and genetic evidence continue to keep phylogenies and our understanding of relationships wavering in key places of the tree such as the relationships of the extinct marine thalattosuchians as well as still living species like gharials. The application of imaging approaches and 3D modeling to both preserved tissues as well as living specimens is now revealing patterns in brain and lung evolution and function, growth strategies, and feeding and locomotor behaviors across the lineage. Comparative anatomical studies are offering new data on genitals, cephalic venous drainage and thoracoabdominal pressures. The new discoveries found here only reveal there is far more work to be done to understand the biology and behavior responsible for the great radiation extinct suchians and their crocodylian descendants experienced during their conquest of Mesozoic and Tertiary ecosystems.